2016
DOI: 10.1103/physreva.93.042702
|View full text |Cite
|
Sign up to set email alerts
|

Pseudopotential for the two-dimensional contact interaction

Abstract: We propose a smooth pseudopotential for the contact interaction acting between ultracold atoms confined to two dimensions. The pseudopotential reproduces the scattering properties of the repulsive contact interaction up to 200 times more accurately than a hard disk potential, and in the attractive branch gives a 10-fold improvement in accuracy over the square well potential. Furthermore, the new potential enables diffusion Monte Carlo simulations of the ultracold gas to be run 15 times quicker than was previou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 59 publications
(124 reference statements)
0
22
0
Order By: Relevance
“…Following Refs. [28][29][30], we propose a UTP that takes a polynomial form within a cutoff radius r c ,…”
Section: B Utpmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Refs. [28][29][30], we propose a UTP that takes a polynomial form within a cutoff radius r c ,…”
Section: B Utpmentioning
confidence: 99%
“…In particular, the cutoff radius should be chosen less than the interparticle spacing so that three-body scattering events are rare; we therefore follow the approach by Refs. [28][29][30] and set r c = 1/k F to balance statistical and systematic errors in the QMC results.…”
Section: B Utpmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the mechanism described by Girardeau whereby the particles can avoid feeling the interaction remains a possibility. In our previous work [20], considering two, three, and four particles [21] in a two dimensional harmonic trap [2,[22][23][24][25][26][27][28][29][30], we showed that interacting bosons avoid feeling the interaction by becoming correlated in such a way that the probability of two particles being at the same position vanishes [31].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically we consider what the requirements are for the basis set to reach the regime of exponential convergence and whether this approach is feasible for multiparticle simulations. Examples of finite-range pseudopotentials used in the literature are the Troullier-Martins [43,44], Pöschl-Teller [45,46], and Gaussian potentials [26,36,[47][48][49][50][51][52][53][54][55][56][57], in addition to the square well popular in diffusion Monte Carlo simulations [48].…”
Section: Introductionmentioning
confidence: 99%